The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1186/s13023-016-0559-z
|View full text |Cite
|
Sign up to set email alerts
|

Moebius sequence –a multidisciplinary clinical approach

Abstract: BackgroundMoebius Sequence (MS) is a rare disorder defined by bilateral congenital paralysis of the abducens and facial nerves in combination with various odontological, craniofacial, ophthalmological and orthopaedic conditions. The aetiology is still unknown; but both genetic (de novo mutations) and vascular events in utero are reported. The purpose of present study was through a multidisciplinary clinical approach to examine children diagnosed with Moebius-like symptoms. Ten children underwent odontological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 23 publications
0
29
0
2
Order By: Relevance
“…44,45 Most patients present normal intelligence, while rare cases of autistic-like behaviors (0%-5%) and mild mental retardation (9%-15%) have been reported. 44,46,47 The syndrome is also referred to as Moebius "sequence," term which defines a cascade of secondary events after an initial insult during the embryonic development, 13,48 as well as a possible genetic etiology 49 (see Box 1).…”
Section: And Vonmentioning
confidence: 99%
“…44,45 Most patients present normal intelligence, while rare cases of autistic-like behaviors (0%-5%) and mild mental retardation (9%-15%) have been reported. 44,46,47 The syndrome is also referred to as Moebius "sequence," term which defines a cascade of secondary events after an initial insult during the embryonic development, 13,48 as well as a possible genetic etiology 49 (see Box 1).…”
Section: And Vonmentioning
confidence: 99%
“…Normal MMOC values have been reported in a 7-year-old child and three older patients (15-19y). 18 Because mastication efficiency results from muscle growth and coordination of the lips, jaws, and cheeks, children with MBS typically show abnormal chewing function. 5 Dysfunction was manifest for a quarter of our population who still needed alterations to food texture at 5 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…5 The term "sequence" is preferred to "syndrome" because it defines a cascade of secondary events after an initial insult during the embryonic period. 6 In histopathologic studies of patients affected by Moebius sequence, the main abnormality is found in the pontine tegmentum where the nuclei for cranial nerve VI are located and the intra-axial fibers of the seventh cranial nerve are crossing posterior to these nuclei (the facial colliculus). 14 Brain stem ischemia during embryogenesis is the most accepted cause of Moebius sequence.…”
Section: Discussionmentioning
confidence: 99%
“…These result in a defect in facial branchiomotor neuron migration, supporting these genes as causative for at least a portion of Moebius sequence cases. 6 Clinically, patients have unilateral or bilateral congenital facial paralysis and esotropia with preservation of the vertical gaze. Known brain MR imaging findings in Moebius sequence are based on small case series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation